Politica e cultura nell’Italia repubblicana : memoria e interpretazioni della Resistenza nella galassia azionista - Leonardo Casalino (Laboratoire Italien)
The author aims at retracing the evolution of the historiographic thought on the Italian Resistance that developed among the members of the “Partito d’Azione” (the “Action Party”), from the Second World War to the present days. This evolution is led by a reflection on the significance of Fascism and Anti-fascism in Italy’s history. The meaning of these words evolves throughout the years after the war as a consequence of political events (the new world order after World War II, the emergence of the communist party…) and a new awareness among former partisans. Reflections on some new concepts such as “rupture”, “revolution”, “civil war”, “betrayed revolution” also emerge. But the overall interpretation of the Resistance by former members of the Partito d’Azione shows the impossibility of protracting an experience that had nonetheless allowed to drag Italian society away from the passivity and resignation weighing on its collective identity.